2021
DOI: 10.1055/s-0041-1724152
|View full text |Cite
|
Sign up to set email alerts
|

Perioral Aerosol Sequestration Suction Device Effectively Reduces Biological Cross-Contamination in Dental Procedures

Abstract: Objective The infection risk during dental procedures is a common concern for dental professionals which has increased due to coronavirus (severe acute respiratory syndrome coronavirus 2) pandemic. The development of devices to specifically mitigate cross-contamination by droplet/splatter is crucial to stop infection transmission. The objective of this study is to assess the effectiveness of a perioral suction device (Oral BioFilter, OBF) to reduce biological contamination spread during dental procedures. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In this study, we observed similar contamination patterns across all suction groups. This is consistent with other reported findings where the use of a saliva ejector (low‐volume suction), high‐volume suction, and extraoral suction results in a reduction of ≤96% of particles generated (Lloro et al, 2021 ; Ou et al, 2021 ; Puljich et al, 2022 ). When comparing saliva ejector to high‐volume suction contamination, the difference was found to be minimal between these groups (D'Antonio et al, 2022 ; Holloman et al, 2015 ; Melzow et al, 2022 ; Yang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, we observed similar contamination patterns across all suction groups. This is consistent with other reported findings where the use of a saliva ejector (low‐volume suction), high‐volume suction, and extraoral suction results in a reduction of ≤96% of particles generated (Lloro et al, 2021 ; Ou et al, 2021 ; Puljich et al, 2022 ). When comparing saliva ejector to high‐volume suction contamination, the difference was found to be minimal between these groups (D'Antonio et al, 2022 ; Holloman et al, 2015 ; Melzow et al, 2022 ; Yang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we focused on the dissemination of droplets and aerosol from an ultrasonic scaler, which has been reported to be the main sources of aerosol and splatter generation in a dental practice (Haffner et al, 2021 ). While other studies commonly used fluorescein, adenosine triphosphate, citric acid, or bacteria as tracers for measuring dispersal, our study is novel in that we are the first to use riboflavin in live patient volunteers (Holliday et al, 2021 ; Lloro et al, 2021 ; Puljich et al, 2022 ; Shahdad et al, 2020 ; Watanabe et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Dental procedures that generate aerosols ("aerosolgenerating procedures") are considered as high-risk mode of SARS-CoV-2 airborne transmission. 4,9 Several reports indicate that ultrasonic scaling procedures are one of the largest major sources of aerosols and droplets 10 that are mainly contaminated with bacteria and viruses. 11 Therefore, safety and infection control procedures are very important to minimize the risk of transmission, one of which is by reducing the number of aerosols and droplets.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the selected protective device is unhandy for everyday use and also not patient compatible. With a suction device (perioral suction device, Oral BioFilter) for perioral aerosol deposition during dental hygiene treatment, contamination of face shields can be prevented as one study showed [ 67 ].…”
Section: Are There Any Other Measures To Protect the Protective Equip...mentioning
confidence: 99%